Investigating the behavioral responses of nektonic and benthic tadpoles elicited by the presence of a predatory nektonic fish - de Souza, Y. C. M. [UNESP]; Annibale, F. S.; Nomura, F.; Rossa‐Feres, D. C. [UNESP] (Wiley, 2025)
Abstract Different defensive strategies are used by tadpoles to avoid or escape from predators, and it is possible that differences in the microhabitat of prey and predators influence the defensive strategies used by tadpoles. Therefore, we experimentally tested whether the presence of a nektonic fish predator ( Oreochromis niloticus ) reduces the time of displacement, increases the latency to start foraging, and reduces the amount of food consumed by nektonic ( Scinax fuscovarius ) and benthic ( Physalaemus nattereri ) tadpoles. Contrary to our expectations, the presence of the predator did not affect the behavior of the nektonic tadpoles. Conversely, however, benthic tadpoles reduced their displacement time in the presence of the predator. It is possible that, due to the ability of nektonic predators to occupy the entire water column, they may trigger defensive behaviors in benthic prey, while the silvery coloring of nektonic tadpoles would reduce their detectability by aquatic predators. Thus, nektonic tadpoles were less reactive toward the presence of predators, despite sharing the same microspatial niche, whereas benthic tadpoles seem to be more reactive toward predators, despite the fact that they do not share their microspatial niche.